(untitled) (Pulse, 2024)
Background: Hamstring tendon auto grafts in the form of quadrupled semitendinosus and gracilis (STG) has become an increasingly used alternative for anterior cruciate ligament (ACL) reconstruction. Bio screw avoids complications by decreasing possibility of graft damage. Current study was designed to evaluate arthroscopic ACL reconstruction with quadrupled semitendinosus auto graft and fixation of the graft by two biodegradable screws in both femur and tibia. Objectives: This study was conducted to evaluate the outcome of arthroscopic ACL reconstruction by semitendinosus tendon autograft using biodegradable screws for both tibia and femur. Methods: 300 patients with ACL injury admitted from January 2010 to December 2015 in the then Apollo Hospitals Dhaka (Evercare Hospital Dhaka now) were enrolled. All patients underwent ACL reconstruction surgery by quadrupled semitendinosus or gracilis auto graft fixed by Bio Screws. After discharge, these patients were followed up for 3 weeks, 3 months and final outcome was recorded after 6 years. Results: 270 patients (90%) had an uneventful post-operative period. 200 patients (66.67%) complained of postoperative pain after 3 weeks, 10 patients (3.33%) complained of knee swelling, 10 (3.33%) patients had infections & 20 patients (6.65%) had knee stiffness after 6 months. Postoperatively, Lachman test improved significantly, grade 0 in 93.33% cases (280 patients) and grade I was in 6.67% cases (20 patients). Anterior drawer test was also markedly improved. Grade 0 was in 93.33% cases (280 patients) and grade I was in 6.67% cases (20 patients). According to the Lysholm Knee Scoring, the final long-term outcome was excellent in 76.67% cases (230 patients), good in 20% cases (60 patients) and fair in 3.33% cases (10 patients). Conclusion: Arthroscopic reconstruction of ACL by quadrupled hamstring autograft fixed by biodegradable screws for both tibia and femur, leads good to excellent results in the majority of the cases. Pulse Vol.15, 2023 P: 9-15